Factors Related to the Appearance of Transverse Bumps in Asphalt Overlays Placed over Crack Sealant. Issue 1 (2017) - Shuler, Scott
Crack sealants often are used as a preservation tool in asphalt pavements. These sealants are placed in cracks to prevent water intrusion into the pavement foundation. Through the reduction of water intrusion, the strength of foundation layers is maintained, and acceptable pavement performance is extended. However, when a hot-mix asphalt overlay is placed on top of a pavement that contains crack sealants, a bump and additional transverse cracks sometimes occur in the new overlay asphalt. These bumps and sometimes transverse cracks are initiated during breakdown rolling and become progressively more severe on further compaction. This paper presents the results of a 5-year study designed to identify factors that related to the appearance of these bumps and consequent cracks. The results of the study indicated that vibratory breakdown rolling, pavement gradient, sealant geometry, tack coat application rate, and tack coat adhesivity were factors that contributed most to the occurrence of bumps and transverse cracks during asphalt overlay construction over crack sealants. Observations suggested that transverse bumps and consequent cracks occurred in proportion to the size of the bow wave of asphalt concrete present immediately in front of the breakdown roller. The increase in the bow-wave size depended on asphalt mixture properties, breakdown roller size, speed, vibration characteristics, and pavement gradient. Three pavement test sections also indicated that the tack coat application rate had an effect on reduction in the appearance of transverse bumps.